THE ROLE OF PEERS IN DEVELOPING OF PARTISIPANTS STUDENTSâ€™ SOCIAL INTELIGENCE IN CLASS VIII D 1 LEMBANG JUNIOR HIGH SCHOOL - Permana, Eva (International Journal Pedagogy of Social Studies, 2018)
ABSTRACTThe background of this research is by the problems found during observation, among them the lack of respect for differences of opinion among students, lack of ability to build closeness with friends other than close friends and lack of empathy that students have. The purpose of this study was to determine the role of peers for improving social intelligence of students. The approach in this study uses a qualitative approach with descriptive methods. The research subjects used were class VIII D students who were determined by purposive sampling. Data collection techniques used in this study were interviews, observation and documentation studies. From the results of the study, it is known that: First, peers provide assistance in improving communication skills so that students are able to build social relations, second, an increase in problem-solving skills, reflected in how students help each other complete tasks, third empathy attitude the participants have increased because students have a sensitivity to the feelings of others, fourth, the attitude of respecting differences of opinion held by students is still lacking, this can be seen from the attitude of students who still insist in maintaining their opinions, fifth, the role peers play a role in increasing the ability to understand and control emotions possessed by students so that they can have a positive impact in dealing with others.Â Keywords: social intelligence, peers, communication skills, empathy, respect for differences